2009
DOI: 10.1093/cercor/bhp102
|View full text |Cite
|
Sign up to set email alerts
|

The Cortical Site of Visual Suppression by Transcranial Magnetic Stimulation

Abstract: In visual suppression paradigms, transcranial magnetic stimulation (TMS) applied approximately 90 ms after visual stimulus presentation over occipital visual areas can robustly interfere with visual perception, thereby most likely affecting feedback activity from higher areas (Amassian VE, Cracco RQ, Maccabee PJ, Cracco JB, Rudell A, Eberle L. 1989. Suppression of visual perception by magnetic coil stimulation of human occipital cortex. Electroencephalogr Clin Neurophysiol 74:458-462.). It is speculated that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 54 publications
2
55
2
Order By: Relevance
“…It has sometimes been assumed that occipital TMS primarily targets the visual area V1 (Boyer et al 2005;Laycock et al 2007;Silvanto et al 2005a, b). However, a recent study (Thielscher et al 2010) found that the exact site of stimulation is likely to be V2d or even V3. In this study, we are largely agnostic with respect to the exact regions in the visual hierarchy that were stimulated, since the net effect of increased noise could be accomplished at several levels in the hierarchy.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…It has sometimes been assumed that occipital TMS primarily targets the visual area V1 (Boyer et al 2005;Laycock et al 2007;Silvanto et al 2005a, b). However, a recent study (Thielscher et al 2010) found that the exact site of stimulation is likely to be V2d or even V3. In this study, we are largely agnostic with respect to the exact regions in the visual hierarchy that were stimulated, since the net effect of increased noise could be accomplished at several levels in the hierarchy.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…One likely reason for such an effect is the presence of variations in brain anatomy and a resulting variability in the amount of direct magnetic stimulation received by each retinotopic region. Understanding how these differences in brain anatomy affect the amount of induced electrical field to each retinotopically defined region of early visual cortex was beyond the scope of this paper, but there has been a lot of exciting work in this direction (Kammer et al 2001;SalminenVaparanta et al 2012aSalminenVaparanta et al , 2012bThielscher et al 2010). Instead, here we focused on the functional consequences of stimulation rather than on the precise amount of stimulation induced in each region.…”
Section: Discussionmentioning
confidence: 99%
“…Following previous research (Boyer et al 2005), we chose the starting point of the hunting procedure to be 2 cm above and 1 cm left of the inion, but the final position was close to the midline for all subjects, and thus it is unlikely that one hemisphere was targeted preferentially. We could not estimate the induced electrical field in each retinotopically defined visual area as has been done before (Kammer et al 2001;SalminenVaparanta et al 2012aSalminenVaparanta et al , 2012bThielscher et al 2010), but instead focused on the functional consequences of stimulation rather than in the precise amount of stimulation induced in each region.…”
Section: Subjectsmentioning
confidence: 99%
“…We cannot pinpoint though, at which time point exactly the posterior mIPS was crucial for information processing. TMS studies in primary visual (Amassian et al, 1989;Thielscher et al, 2010) and motor (Di Lazzaro et al, 1999;Ferbert et al, 1992) areas, and TMS connectivity studies between higher order and primary motor cortices (Koch et al, 2007;Mochizuki et al, 2004) succeeded in narrowing down chronometry of neural processing to time windows of few milliseconds. Those effects, however, are much more robust than TMS effects due to virtual lesions of higher cortical areas such as the posterior parietal cortex.…”
Section: Discussionmentioning
confidence: 99%